A review of internal and external influences on corporate governance and financial accountability in Nigeria. (2015) - Okike, Elewechi; Adegbite, Emmanuel; Nakpodia, Franklin; Adegbite, Stephen
No country exists in isolation, and as developing countries like Nigeria aspire to 'international' standards of accountability and governance suited to the developed economies, they are confronted with the reality that it is difficult to separate the socio-cultural context in which they operate from the external pressures to conform. This literature review provides deep insights into the developments in corporate governance and accountability in Nigeria, and in particular the influence of internal and external factors. While the extant literature suggests that the lack of corporate governance structures limits improvements in developing economies, we argue that the appropriateness, and the effectiveness of regulatory compliance systems explains corporate governance infractions in the country. We contribute to comparative corporate governance discourse, presenting important implications for key players in corporate governance development and monitoring, across global polity and practice.